2013
DOI: 10.1039/c3nr01542d
|View full text |Cite
|
Sign up to set email alerts
|

Efficient and stable CH3NH3PbI3-sensitized ZnO nanorod array solid-state solar cells

Abstract: We report for the first time the use of a perovskite (CH 3 NH 3 PbI 3 ) absorber in combination with ZnO nanorod arrays (NRAs) for solar cell applications. The perovskite material has a higher absorption coefficient than molecular dye sensitizers, gives better solar cell stability, and is therefore more suited as a sensitizer for ZnO NRAs. A solar cell efficiency of 5.0% was achieved under 1000 W m À2 AM 1.5 G illumination for a solar cell with the structure: ZnO NRA/CH 3 NH 3 PbI 3 /spiro-MeOTAD/Ag. Moreover,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
193
1
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 279 publications
(205 citation statements)
references
References 32 publications
5
193
1
3
Order By: Relevance
“…[17][18][19][20][21][22][23][24] Moreover, the conductivity of ZnO is several orders of magnitude higher than the TiO 2 one and that favors the electron transport toward the front contact. 25,26 Kelly et al 21 have recently reported remarkably high efficiency PSCs using a thin layer of dense planar ZnO prepared by spin-coating.…”
Section: 16mentioning
confidence: 99%
“…[17][18][19][20][21][22][23][24] Moreover, the conductivity of ZnO is several orders of magnitude higher than the TiO 2 one and that favors the electron transport toward the front contact. 25,26 Kelly et al 21 have recently reported remarkably high efficiency PSCs using a thin layer of dense planar ZnO prepared by spin-coating.…”
Section: 16mentioning
confidence: 99%
“…Another possible explanation would be a reduced electronic coupling of P3HT to CH 3 NH 3 PbI 3 , but it seems to be improbable because Bi et al measured electron lifetime in perovskite/SpiroOMeTAD and perovskite/P3HT systems and attributed the longer electron lifetime in perovskite/Spiro-OMeTAD to worse coupling due to the spiro shape. 28 In conclusion, we have shown that hole transfer from photoexcited CH 3 NH 3 PbI 3 to P3HT occurs on a time scale of a few nanoseconds and from the thermally relaxed perovskite. The rate of hole transfer was found to be independent of excess excitation energy.…”
mentioning
confidence: 99%
“…Since the¯rst reports, 6,7 the solid state perovskite solar cell has been developed very fast to reach a power conversion e±ciency (PCE) above 15%. 8,9 Several studies have reported on solar cell structure, 7,[10][11][12] alternative organic materials, [13][14][15] charge transport mechanism, [16][17][18] perovskite preparing methods, 8,19,20°e xible solar cell, [21][22][23] and modules. 24 Although perovskite solar cell can also work without hole transport material (HTM), with a PCE of 5-8%, 12,25 transient absorption results show that the most e±cient charge separation is obtained when using TiO 2 and HTM together.…”
Section: Introductionmentioning
confidence: 99%